Efektifitas Lama Perendaman ZPT Ekstrak Daun Kelor dan Kombinasi Media Tanam Terhadap Panjang Akar Bibit Kopi Robusta (Coffea canephora var. robusta) - Br Sitepu, Sri Mahareni; Zamriyeti, Zamriyeti; Luta, Devi Andriani; Syahfitri, Windi Ely (UNIVERSITAS LABUHANBATU, 2024)
Coffee beans are covered in a hard shell so they take a long time to germinate. The length of germination time will affect coffee growth and production. To speed up the germination of coffee beans, growth regulators can be used. Apart from that, the growth of coffee plants can also be influenced by the planting media used to live and obtain nutrients. This research used a Complete Randomized Block Design (RAK) with 2 factors and 3 blocks to obtain 36 research plots. Factor 1: soaking time for growth regulators in Moringa leaf extract (T) consisting of 4 levels: T0: 0 hours, T1: 6 hours, T2: 12 hours, T3: 18 hours. Factor 2: The combination of planting media denoted by (M) consists of 4 levels: M0: topsoil, M1: topsoil + rice husk charcoal + goat dung (2:1:1), M2: topsoil + charcoal rice husks + chicken manure (2:1:1). The research results showed that the soaking time for the growth regulator, Moringa leaf extract, did not have a significant effect on the root length of Robusta coffee plants, but the combination of planting media had a significant effect on the root length of Robusta coffee plants. Keywords : robusta coffee, live and obtain nutrients, moringa leaf